Managemen Kurikulum Merdeka Berbasis Teoritis dan Filosofis - Mahdin, Maulian Hi; Yahiji, Kasim; Abdullah, Abdul Haris (JURNAL PENA EDUKASI, 2024)
Abstract: This research aims to examine theoretical and philosophical-based curriculum management. The method used is a qualitative approach with a literature study method. The data used comes from relevant books, journals, and scientific articles. The research results show curriculum management includes planning, organizing, implementing, and evaluating the curriculum. Theoretically, curriculum management is related to increasing the efficiency of resource use, fairness, and opportunities for students and the relevance and effectiveness of learning. Philosophically, character-based curriculum management aligns with the national education goal of forming students with morals. In conclusion, curriculum management requires integrating theoretical and philosophical aspects to achieve comprehensive educational goals, including improving teacher performance and the effectiveness of the teaching and learning process and empowering curriculum components efficiently and effectively.Keywords: curriculum management on a theoretical; philosophical basis.Abstrak: Penelitian ini bertujuan untuk mengkaji manajemen kurikulum berbasis teoritis dan filosofis. Metode yang digunakan adalah pendekatan kualitatif dengan metode studi literatur. Data yang digunakan berasal dari buku, jurnal, dan artikel ilmiah yang relevan. Hasil penelitian menunjukkan bahwa manajemen kurikulum mencakup perencanaan, pengorgan-isasian, pelaksanaan, dan evaluasi kurikulum. Secara teoritis, manajemen kurikulum berhub-ungan dengan peningkatan efisiensi pemanfaatan sumber daya, keadilan, dan kesempatan bagi siswa, serta relevansi dan efektivitas pembelajaran. Secara filosofis, manajemen kurikulum berbasis karakter sejalan dengan tujuan pendidikan nasional untuk membentuk peserta didik yang berakhlak. Adapun kesimpulan dari penelitian ini, manajemen kurikulum memerlukan integrasi antara aspek teoritis dan filosofis untuk mencapai tujuan pendidikan yang kompre-hensif, termasuk peningkatan kinerja guru dan efektivitas proses belajar mengajar serta pem-berdayaan komponen kurikulum secara efisien dan efektif.Kata kunci: managemen kurikulum berbasis teoritis; filosofis.